Primal-Dual Method of Solving Convex Quadratic Programming Problems - V. Moraru (Computer Science Journal of Moldova, 2000)
This paper presents a primal-dual method for solving quadratic programming problems. The method is based on finding an exact solution of a finite sequence of unconstrained quadratic prigraamming problems and on finding an aproximative solution of constrained minimization problem with simple constraints. The subproblem with simple constraints is solved by the interior-reflective Newton's method [6].